(untitled) (Journal of Parents and Teachers, 2014)
The article details the nature and pedagogical value of role-playing games. In order to do so, the author makes comparisons between what is truly a game of this type and what is far from being one. Thus, the author analyzes their origin as well as the procedure for their correct development. In addition, the pedagogical utilities such as decision making, creativity or interest, are exposed. Finally, the author reports on the best-known and best-selling role-playing games